Fiberoptic hemodynamic spectroscopy reveals abnormal cerebrovascular reactivity in a freely moving mouse model of Alzheimer’s disease - Gareau, Daniel S.; RochaKim, Nicholas; Choudhury, Arnab; Bamkole, Michael; Snuderl, Matija; Zou, Julia; Yaroslavsky, Anna; Jacques, Steven L.; Strickland, Sidney; Krueger, James G.; Ahn, Hyung Jin (Frontiers in Molecular Neuroscience, 2023)
Many Alzheimer’s disease (AD) patients suffer from altered cerebral blood flow and damaged cerebral vasculature. Cerebrovascular dysfunction could play an important role in this disease. However, the mechanism underlying a vascular contribution in AD is still unclear. Cerebrovascular reactivity (CVR) is a critical mechanism that maintains cerebral blood flow and brain homeostasis. Most current methods to analyze CVR require anesthesia which is known to hamper the investigation of molecular mechanisms underlying CVR. We therefore combined spectroscopy, spectral analysis software, and an implantable device to measure cerebral blood volume fraction (CBVF) and oxygen saturation (SO2) in unanesthetized, freely-moving mice. Then, we analyzed basal CBVF and SO2, and CVR of 5-month-old C57BL/6 mice during hypercapnia as well as during basic behavior such as grooming, walking and running. Moreover, we analyzed the CVR of freely-moving AD mice and their wildtype (WT) littermates during hypercapnia and could find impaired CVR in AD mice compared to WT littermates. Our results suggest that this optomechanical approach to reproducibly getting light into the brain enabled us to successfully measure CVR in unanesthetized freely-moving mice and to find impaired CVR in a mouse model of AD.